Super-resolution imaging and its applications - Xu, Di. (2011)
Super Resolution is an image processing technique that aims to generate high resolution (HR) images by utilizing a sequence of sub-pixel shifted low resolution (LR) images. During the past twenty years, most of the SR techniques have been applied on regular images taken with a hand-held camera. However, application of SR in the field of biomedicine is a state-of-the-art area for research. In fact, SR has not yet been applied in a Photo-thermal Imaging (PTI) system which provides a resolution exceeding the diffraction limit.